Adsorption properties and mechanism of barium (II) and strontium (II) removal from fracking wastewater using pecan shell based activated carbon. (20th August 2018) - Kaveeshwar, Aditya Rajeev; Kumar, Ponnusamy Senthil; Revellame, Emmanuel D.; Gang, Daniel D.; Zappi, Mark E.; Subramaniam, Ramalingam
Abstract: Hydraulic fracturing generates wastewater ranging from 2 to 8.5 million gallons (7.5–32 million liters per well) per well. Suspended solids, total dissolved solids, hydrocarbons, organic compounds, and heavy metals are some of the common contaminants present in the fracking wastewater. In this work, pecan shell-based activated carbon (PSBAC) was prepared, characterized, and applied for the removal of Ba(II) and Sr(II) from synthetic fracking wastewater. The PSBAC had a high specific surface area of 1517 m 2 /g and pore volume of 0.8 cm 3 /g. Results showed that the Langmuir model best fits the adsorption system with the PSBAC having maximum adsorptive capacity of 3.33 mg/g for Ba(II) and 8.8 mg/g for Sr(II). Pseudo-second order kinetic model had the best fit, indicating chemisoprtion as the rate limiting step. Kinetic studies revealed that for both metals, sorption was not limited by intraparticle diffusion. The adsorption process was thermodynamically favorable and endothermic in nature. Graphical abstract: Clean water Source: https://www.acs.org/content/acs/en/pressroom/presspacs/2011/acs-presspac-november-9-2011/weird-world-of-water-gets-a-little-weirder.html . Image Highlights: Pecan shell based activated carbon (PSBAC) was developed and characterized. Adsorption properties and mechanism of Barium(II) and Strontium(II) removal was studied. Kinetic studies revealed that the adsorption followed chemisorption. Thermodynamic studies shown that adsorption was feasible and endothermic in nature.